Thrombolysis, time-to-treatment and in-hospital outcomes among young adults with ischaemic stroke in China: findings from a nationwide registry study in China - Wang, Hai-Yan; Gu, Hong-Qiu; Zhou, Qi; Jiang, Ying-Yu; Yang, Xin; Wang, Chun-Juan; Zhao, Xing-Quan; Wang, Yi-Long; Liu, Li-Ping; Meng, Xia; Li, Hao; Liu, Chelsea; et al. (BMJ open, 2022)
Background and purposeWe aimed to determine whether young adults (<50 years) with acute ischaemic stroke (AIS) are more likely to receive intravenous tissue plasminogen activator (IV tPA) and have shorter time to treatment than older patients with stroke.MethodsWe analysed data from the Chinese Stroke Center Alliance registry for patients with AIS hospitalised between August 2015 and July 2019. Patients were classified into two groups according to age: young adults (<50 years of age) and older adults (≥50 years of age).ResultsOf 793 175 patients with AIS admitted to 1471 hospitals, 9.1% (71 860) were young adults. Compared with older adults, a higher proportion of young adults received IV tPA among patients without contraindicaitons (7.2% vs 6.1%, adjusted OR (aOR) 1.13, 95% CI 1.10 to 1.17) and among patients without contraindications and with onset-to-door time ≤3.5 hours (23.6% vs 19.3%, aOR 1.20, 95% CI 1.15 to 1.24). We did not observe differences in onset-to-needle time (median hours 2.7 hours) or door-to-needle time (DNT) (median minutes 60 min) between young and older adults. The proportion of DNT ≤30 min, DNT ≤45 min and DNT ≤60 min in young and older IV tPA-treated patients were 16.9% vs 18.8%, 30.2% vs 32.8% and 50.2% vs 54.2%, respectively. Compared with older adults, young adults treated with IV tPA had lower odds of in-hospital mortality (0.5% vs 1.3%, aOR 0.54, 95% CI 0.35 to 0.82) and higher odds of independent ambulation at discharge (61.0% vs 53.6%, aOR 1.15, 95% CI 1.08 to 1.22), and the associations may be partly explained by stroke severity measured by the National Institutes of Health Stroke Scale score.ConclusionYoung adults with AIS were more likely to receive IV tPA than older adults, although there was no difference between the two groups in time to treatment. Compared with older adults, young adults may had better in-hospital outcomes.